Antibacterial isoamphipathic oligomers highlight the importance of multimeric lipid aggregation for antibacterial potency. (December 2018) - Brown, Joseph; Mohamed, Zeinab; Artim, Christine; Thornlow, Dana; Hassler, Joseph; Rigoglioso, Vincent; Daniel, Susan; Alabi, Christopher
Abstract Cationic charge and hydrophobicity have long been understood to drive the potency and selectivity of antimicrobial peptides (AMPs). However, these properties alone struggle to guide broad success in vivo, where AMPs must differentiate bacterial and mammalian cells, while avoiding complex barriers. New parameters describing the biophysical processes of membrane disruption could provide new opportunities for antimicrobial optimization. In this work, we utilize oligothioetheramides (oligoTEAs) to explore the membrane-targeting mechanism of oligomers, which have the same cationic charge and hydrophobicity, yet show a unique 10-fold difference in antibacterial potency. Solution-phase characterization reveals little difference in structure and dynamics. However, fluorescence microscopy of oligomer-treatedStaphylococcus aureus mimetic membranes shows multimeric lipid aggregation that correlates with biological activity and helps establish a framework for the kinetic mechanism of action. Surface plasmon resonance supports the kinetic framework and supports lipid aggregation as a driver of antimicrobial function. Joseph Brown et al. use oligothioetheramides (oligo TEAs) to show that multimeric lipid aggregation inStaphylococcus aureus mimetic membranes correlates with the biological activity of oligoTEAs. These results may explain why antimicrobial peptides with identical cationic charge and hydrophobicity show different biological activity.